Determinants of capital structure and the effects towards debt ratio of listed construction companies in Malaysia / Anis Nabillah Rozwan Affandi - Rozwan Affandi, Anis Nabillah (Faculty of Business Management, 2014)
Construction companies are in an undeniable state that they could not survive and continue their daily operations without sufficient level of the working capital. This indicates that in today’s financial management, achieving the best capital structure for each firm is very crucial. The construction industry also facing lack of capital problem to some extent thus contribute to higher failure rate of construction companies. This paper intends to determine the factors of the contribution to the capital structure of construction firms listed in the Bursa Malaysia market. The data ranges from 2000 to 2013 on a yearly basis. The sample data were derived from financial statements of eight construction companies listed in Bursa Malaysia market with a number of observations totalling 104. Debt ratio is the dependent variable and expressed by formula; total liabilities divided by total assets. The independent variables are profitability, size of company, growth opportunity and liquidity. The results show that the profitability of the construction companies is significant negatively relations to debt ratio while size of company, growth opportunity and liquidity are insignificant in relations to total debt by using panel data method. This indicated that lower profit is the results obtained from using more debt for construction companies. The results also suggest that the companies are depending more on debt financing as to equity financing for expansion and growth.